IDENTIFIKASI BAKTERI DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK BAKTERI ENDOFIT YANG DIISOLASI DARI ALGA MERAH (Gracilaria sp.) - Fittrie Meyllianawaty Pratiwy; Fajar Nurul Arifah (LPPM Universitas Negeri Jakarta, 2022)
Glacilaria sp. is one type of red algae that is widely found in Indonesia. Red algae has anti-microbial, anti-bacterial, anti-viral, anti-fungal, and other benefits. Endophytic microbes associated with seaweeds such as bacteria and fungus are thought to be able to produce the same bioactive compounds as their host, seaweeds. Several studies have also shown that the antibacterial activity of endophytic microbes can inhibit pathogenic bacteria. This study was conducted to identify endophytic bacteria present in Glacilaria sp. in inhibiting the growth of pathogenic bacteria (Vibrio sp. and S. aureus). Endophytic bacteria found in Gracilaria sp. isolated and tested for antibacterial activity using Staphylococcus aureus and Vibrio sp. bacteria. with disc disc method. the results showed that endophytic bacteria of the red algae Gracilaria sp. has antibacterial activity against bacteria S. aureus and Vibrio sp. It has inhibitory zones of 8 mm and 7.6 mm, respectively